A Closer Look at the Vertebral Arteries - Rajani Singh (Highlights on Medicine and Medical Research Vol. 6, 2021)
Cerebral aneurysm and posterior circulation stroke are very dangerous and/or fatal disease pertaining to variant and/or anomalous vertebral arteries. Besides, if subclavian artery is occuluded, this causes antegrade and retrograde flow (subclavian steal syndrome). The first two diseases described above are caused by vertebral artery anomalies whereas the last one, subclavian steal syndrome involves vertebral artery but is caused by occulusion of subclavian artery. Therefore, a thorough comprehension of vertebral artery anomalies is of paramount importance while performing diagnostic and interventional angiography for vascular, cardiothoracic, head, neck and anterior cervical surgery. Therefore variations of vertebral arteries and their configuration are described in this chapter. Vertebral arteries are one of the principal arteries irrigating brain specifically spinal cord, medulla and part of cerebellum. There are two vertebral arteries, one on each side of the neck. Each vertebral artery sprouts from the postero-superior aspect of 1st part of bilateral subclavian artery at the root of neck. These follow a long course and end in the cranial cavity by uniting with their counterpart forming basilar artery at the lower border of pons. Their courses are divided into four parts. The first three segments are extracranial and the last one is intracranial. Besides, originating from subclavian artery, left vertebral arteries is also reported to arise from the aortic arch between left common carotid artery and left subclavian artery or lateral to it and also from a common trunk formed by left subclavian and left vertebral artery but the right vertebral artery emanate from thyrocervical trunk, the brachiocephalic trunk, the common carotid artery and external carotid artery. Beside these variations, there may be agenesis, hypoplasia, stenosis and asymmetry of these arteries. Agenesis, hypoplasia, asymmetry and stenosis of vertebral arteries may cause cerebral aneurysm and posterior circulation stroke besides, iatrogenic complications. Thus knowledge of vertebral artery is of utmost use in preventing misdiagnosis and mismanagement of diseases pertaining to vertebral arteries. Therefore, the objective of this chapter is to give clear picture of normal vertebral arteries and description of variations coupled with anomalies to diagnose these diseases by imagery (ultrasound, angiography or MRI) in association with signs and symptoms. The knowledge of normal and variant Anatomy of vertebral arteries is very essential which has been described vividly in this chapter.